A Method for Identifying the Public Good Allocation Process Within a Group - McGuire, M. C.; Groth, C. H. (Quarterly Journal of Economics, 1985)
This paper develops a method for inferring from observations on a group's collective expenditure whether a cooperative or competitive resource allocation process, or some mixture of the two, has occurred. The method will be applicable to a variety of situations from small collectives such as the family or groupings of nations collaborating in security or trade alliances, to collectives with large numbers. This method will be useful for identifying (1) whether observed outcomes have been efficient, (2) whether costs have been shared equitably, (3) what is the form of collaboration or competition, and (4) what is the degree of “publicness” of the collective good.